2003
DOI: 10.2136/sssaj2003.1168
|View full text |Cite
|
Sign up to set email alerts
|

Organic Phosphorus Composition and Potential Bioavailability in Semi-Arid Arable Soils of the Western United States

Abstract: The organic P composition of semi-arid arable soils is largely unknown, but such information is fundamental to understanding P dynamics in irrigated agriculture. We used solution "P nuclear magnetic resonance (NMR) spectroscopy and phosphatase hydrolysis to characterize organic P in semi-arid arable soils from the western USA (organic C 2.0-30.7 g C kg' soil, clay 2-48%, pH 5.2-8.2, CaCO 3 <1-480 g kg -' soil). Total P concentrations ranged from 220 to 1210 mg P kg-' soil, of which between 12 and 45% was extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
119
1
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(144 citation statements)
references
References 43 publications
23
119
1
1
Order By: Relevance
“…The hypothesis that non-biomass organic phosphorus dominates in bicarbonate extracts is supported by the speciation of phosphorus in such extracts, which is dominated by phosphate monoesters and is, therefore, similar to the whole-soil organic phosphorus extracted in strong alkaline solution [63,64].…”
Section: Soilsmentioning
confidence: 95%
“…The hypothesis that non-biomass organic phosphorus dominates in bicarbonate extracts is supported by the speciation of phosphorus in such extracts, which is dominated by phosphate monoesters and is, therefore, similar to the whole-soil organic phosphorus extracted in strong alkaline solution [63,64].…”
Section: Soilsmentioning
confidence: 95%
“…However, surprisingly few researchers have examined the role of climate on soil organic P. Turner et al (2003a) suggested that climate was a key driver of the low SOM concentrations reported for a series of semiarid arable cropping soils. The authors found that decreasing organic P concentrations correlated with increasing temperatures, whereas soil organic P increased with increasing precipitation.…”
Section: Introductionmentioning
confidence: 99%
“…The same results were also discovered in soil samples, but not in sediments at the regional scale (McDoell and Stewart, 2006;Dou et al, 2009). Turner et al (2003a) suggested that higher adsorptive surface area and lower microbial activity are beneficial for the existence of Po. On the contrary, alkaline soil, which is mainly characterized by CaCO 3 , has a lower ability for holding organic carbon and Po, so the NaOH-EDTA had a weak ER in extracting Po from calcicolous soil (Turner et al, 2003a).…”
Section: Edta-naoh Extraction Rate and Characteristics Of Sedimentmentioning
confidence: 99%
“…Turner et al (2003a) suggested that higher adsorptive surface area and lower microbial activity are beneficial for the existence of Po. On the contrary, alkaline soil, which is mainly characterized by CaCO 3 , has a lower ability for holding organic carbon and Po, so the NaOH-EDTA had a weak ER in extracting Po from calcicolous soil (Turner et al, 2003a). In this study, the reason that ER and pH show a positive relationship is that acidic sediment, which has a higher ability to hold organic matter than alkaline sediment, was distributed in southern China.…”
Section: Edta-naoh Extraction Rate and Characteristics Of Sedimentmentioning
confidence: 99%